Simulation and Calculation of Assembly Error of Linear Ion Trap - Xiao-long LI; Wei-min WANG; Fu-xing XU; Chuan-fan DING (Zhipu Xuebao)
As the core part of the portable mass spectrometers, the ion trap mass analyzer is equivalent to the "engine", which determines the analytical capability of the mass spectrometer. Ion trap mass analyzers require a high degree of precision in both machining and assembly. However, there will inevitably be certain errors in the actual machining and assembly processes of the ion trap, which introduce the high-order field of some components and affect the analytical performance of the ion trap mass analyzer, thereby causing the analytical performance of the mass spectrometer to deteriorate. In this paper, when the mass resolution remained stable, the tolerated maximum assembly error for a ion trap mass analyzer was discussed. On the basis of the hyperboloid linear ion trap structure, the resolution of the ion trap was improved by optimizing the tensile distance Δrx of the x electrode in the ion exit direction, and a reasonable high-order electric field was introduced. The ion trap was modeled by SIMION software, PAN33 software was used to analyze the internal electric field distribution of a hyperboloid linear ion trap, and AXSIM software was used to simulate ion motion trajectories and mass spectra. The results showed that when Δrx is 0.9 mm, by optimizing parameters such as the alternating voltage (AC) amplitude and frequency, the best mass resolution of the hyperboloid linear ion trap reach 3 958 at m/z 609. Then, three cases of assembly error in the x, y and xy directions were discussed, and the step size of each error variable was 0.01 mm (10 microns), and the simulation studies were successively given. When the assembly error in the x, y and xy directions are less than 0.06, 0.06, 0.04 mm, respectively, the resolution is relatively stable, which can provide a reference for the subsequent actual assembly error.